2021
DOI: 10.1155/2021/5550776
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Trabeculectomy in Uveitic Glaucoma: A Long-Term, Single-Center, Retrospective Case-Control Study

Abstract: Purpose. To evaluate the long-term outcomes of trabeculectomy with mitomycin C (MMC-TLE) in patients with uveitic glaucoma (UG). Patients and Methods. This was a retrospective, nonrandomized case series study. MMC-TLE was performed on 50 eyes with UG between February 2001 and January 2015 at Hokkaido University Hospital. Age- and sex-matched patients with primary open angle glaucoma (POAG) who underwent MMC-TLE were matched by age and sex and enrolled as controls. Surgical success was defined as an intraocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Previous studies have reported variable risk factors associated with surgical failure in uveitic glaucoma after trabeculectomy, including immediate postoperative IOP spike, early laser suture lysis [ 26 ], male sex [ 19 ], and postoperative exacerbation of inflammation [ 29 ]. Our results indicated that previous history of cataract operation was the only protective factor against surgical failure in patients with uveitic glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported variable risk factors associated with surgical failure in uveitic glaucoma after trabeculectomy, including immediate postoperative IOP spike, early laser suture lysis [ 26 ], male sex [ 19 ], and postoperative exacerbation of inflammation [ 29 ]. Our results indicated that previous history of cataract operation was the only protective factor against surgical failure in patients with uveitic glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for such association is not yet proven, and in fact, the results as reported in the relevant prior studies have been contradictory. For example, one study found no association between previous cataract surgery and trabeculectomy [ 29 ], whereas another study reported that previous cataract surgery had a negative effect on both trabeculectomy and Ahmed valve implantation, albeit with only marginal significance [ 17 ]. We performed an additional comparative analysis between pseudophakic ( n = 17) and phakic ( n = 21) eyes, but no difference in their baseline characteristics was found.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we conducted a similar study on TLE for UG which showed that the surgical outcome for UG was not inferior to that of POAG. 25 We ordinarily choose S-LOT for patients with early to mid-stage glaucoma and TLE for patients with advanced glaucoma, considering a risk of central vision loss because of IOP spikes after S-LOT. Our 2 studies had similar results, although the severity of visual field defects in the patients was different.…”
Section: Discussionmentioning
confidence: 99%
“…At the 6-year mark, 67% of patients had an IOP of less than 18 mmHg and 52% had an IOP of less than 15 mmHg. At the 10-year follow-up, it was noted that 67% of patients still had an IOP of less than 18 mmHg, and 48% of patients had an IOP of less than 15mmHg [21 ▪ ]. Lee et al quoted similar results of 86% of uveitic glaucoma patients achieving IOP less than 21 mmHg, with or without medication posttrabeculectomy with MMC at 6 months and 82% at the 1 year mark [23].…”
Section: Conventional Surgical Optionsmentioning
confidence: 95%